Heart transplant in a patient with persistent left superior vena cava - G. V. Aniskevich; G. A. Sadrieva; V. N. Poptsov; E. A. Spirina; V. I. Orlov; R. Sh. Saitgareev (Вестник трансплантологии и искусственных органов, 2021)
Objective: to present our own experience of heart transplantation in a patient with persistent left superior vena cava (PLSVC). A clinical case of successful orthotopic heart transplantation using the biatrial technique in a patient with PLSVC drainage into the right atrium is presented. The clinical effect achieved as a result of the treatment fully justifies the chosen surgical tactics and allows us to recommend the proposed tactics for treatment of such a rare anomaly. Conclusion. The clinical effect achieved as a result of the treatment fully justifies the chosen surgical tactics and allows us to recommend the proposed tactics for treatment of such a rare anomaly.